Effect of nano silica coating concentration on reducing acrylic resin denture cytotoxicity - Gene Rizky Natalia Gunawan; Titik Ismiyati; Haryo Mustiko Dipoyono (Majalah Kedokteran Gigi Indonesia, 2019)
Acrylic resin is a denture base material mostly used in the fabrication of removable partial denture and complete denture because it is easy to process, economical and aesthetically satisfying. However, the acrylic resin has a weakness i.e. residual monomer content which causes cytotoxic effect to human cells. Nano-silica coating could be used on the acrylic resin to reduce residual monomer content. The purpose of this study was to determine the effect of nano-silica coating concentration on the cytotoxicity of acrylic resin denture base material. Twenty-four acrylic resin disc-shaped specimens (5 mm in diameter and 2 mm in thickness) were divided into 4 groups (n=6), i.e. control, group with application of 0.5%,1%, and 2% nano silica coating. The specimens on the silica coating groups were silica coated using dip-coating method. After the coating was completed, the specimens were added into cell fibroblast culture (vero cell line). Cytotoxicity testswere done by MTT assay. The optical density was measured using ELISA plate reader to determine the percentage of cell viability. The highest mean of cell viability was shown in 0.5% concentration (96.78 ± 1.71) and the lowest mean was shown in the control group (80.32 ± 6.53). One-way ANOVA showed that there were significant differences among these groups. LSD tests showed that there was significant difference among all of the groups. This study concluded that nano silica coating concentration has a significant effect on the cytotoxicity of acrylic resin denture base materials.